Seasonal development and differential retention of ice algae and other organic fractions in first-year Arctic sea ice - Juhl, AR; Krembs, C; Klaus Meiners (2011)
The temporal evolution of ice algae biomass, particulate and dissolved organic carbon (POC and DOC), and particulate and dissolved carbohydrates (pCHO and dCHO) was followed in land-fast, Arctic sea ice near Barrow, Alaska, USA. POC, DOC, pCHO, and dCHO were found in young ice before algal growth occurred, indicating initial allochthonous sources. In sediment-free ice, particulate organic pools (POC and pCHO) were more strongly related to ice algae biomass than the larger dissolved organic pools (DOC and dCHO). Although algae biomass peaked near the ice bottom, integrating across ice depth showed that most organic matter was found above the bottom layer. Sediment-containing ice held high organic matter concentrations, although peak ice algae biomass was lower than in sediment-free ice. Sediments incorporated in sea ice can be a source of allochthonous organic matter that is comparable to autochthonous contributions by ice algae. In late spring, much of the algae biomass in sediment-free ice was lost, in as little as 5 d. Nevertheless, large POC, DOC, pCHO, and dCHO pools remained in the ice, both near the bottom and in upper layers. Observations of natural ice cores melting in laboratory experiments demonstrated a network of extracellular polymeric substances (EPS) remaining attached to the ice bottom, even as the ice structure melted away. This retained EPS may partly explain the POC and carbohydrate pools found in sea ice after the loss of algae. Differential retention of organic matter by seasonal sea ice suggests that the characteristics of material exported from the ice will change as the melt season progresses.